2017
DOI: 10.1038/s41598-017-07851-z
|View full text |Cite
|
Sign up to set email alerts
|

Luciferase Expression Allows Bioluminescence Imaging But Imposes Limitations on the Orthotopic Mouse (4T1) Model of Breast Cancer

Abstract: Implantation of reporter-labeled tumor cells in an immunocompetent host involves a risk of their immune elimination. We have studied this effect in a mouse model of breast cancer after the orthotopic implantation of mammary gland adenocarcinoma 4T1 cells genetically labelled with luciferase (Luc). Mice were implanted with 4T1 cells and two derivative Luc-expressing clones 4T1luc2 and 4T1luc2D6 exhibiting equal in vitro growth rates. In vivo, the daughter 4T1luc2 clone exhibited nearly the same, and 4T1luc2D6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 53 publications
7
80
1
Order By: Relevance
“…After successfully establishing and optimizing imaging‐guided protocol in the subcutaneous U87MG tumor model, we further performed NIR‐II imaging‐guided sentinel LN surgery in a breast cancer model since this technology is commonly used in breast cancer ( Figure a). We first used luciferase‐transfected 4T1 cells for subcutaneous inoculation . The bioluminescence of 4T1 cells allowed us to determine whether cancer has spread beyond the primary tumor into the lymphatic system.…”
mentioning
confidence: 99%
“…After successfully establishing and optimizing imaging‐guided protocol in the subcutaneous U87MG tumor model, we further performed NIR‐II imaging‐guided sentinel LN surgery in a breast cancer model since this technology is commonly used in breast cancer ( Figure a). We first used luciferase‐transfected 4T1 cells for subcutaneous inoculation . The bioluminescence of 4T1 cells allowed us to determine whether cancer has spread beyond the primary tumor into the lymphatic system.…”
mentioning
confidence: 99%
“…Injecting three times more cells (3x10 6 ), to optimize the chances of tumor implantation, did not dramatically increase the percentage of mice developing a progressive CRC profile, thus implying that the number of injected cancer cells has a negligible impact on the two CRC developmental profiles. Although rarely observed in B6 mice [40], increased immunogenicity linked to the expression of luciferase in tumor cells was previously described in other tumor mouse models [41]. However, since the outcome of orthotopic parental MC38 tumors was the same as that of MC38-fLuc IC-tumors, we concluded that luciferase immunogenicity could not explain the CRC rejection profile.…”
Section: Discussionmentioning
confidence: 51%
“…Bioluminescence in vivo imaging system (IVIS) using luciferase reporter containing cell lines has been commonly utilized to track tumor growth over time, but this technique has limitations. This imaging technique involves injection of luciferin in conjunction with tumor cells, which is invasive and can initiate an inflammatory response [18]. Additionally, this technique only provides qualitative information regarding tumor progression [17].…”
Section: Introductionmentioning
confidence: 99%